Leksem Tebing dalam Tanjak Melayu: Kajian Semantik Inkuisitif - M. Zafran Syaira; Hermandra Hermandra; Elmustian Elmustian (Badan Pengembangan dan Pembinaan Bahasa, 2026)
This study aims to reveal the meaning and lexem domain of the cliffs in the naming of tanjak Melayu, especially on Tanjak Tebing Tinggi, Tebing Runtuh, and Tebing Laksamana, in the cultural context of the Malay community through an inquisitive semantic approach. This study uses qualitative descriptive method. Data in the form of phrases, sentences, and images related to the names of tanjak Melayu were collected through observation, interview, and documentation techniques, with data sources coming from the book headband Alam Melayu (origins, history and usage) by Johan Iskandar and interviews with speakers from The Serai Serumpun community. Data analysis is carried out through three stages, namely scripting semantics, cognitive semantics, and inquisitive semantics. The results showed that the lexemes of the cliff is interpreted as a symbol of defense that represents firmness, protection, and endurance in Malay culture. Specifically, Tanjak Tebing Tinggi is interpreted as a symbol of Defense and is in the domain of power, tanjak Tebing Runtuh is interpreted as a symbol of success in defending the territory, and tanjak Tebing Laksamana is interpreted as a symbol of successful leaders in defending the territory, both of which are in the service domain. The naming of tanjak berleksem tebing is eventful because it is based on the historical and symbolic experience of the Malay community in the context of defense and leadership. Abstrak Penelitian ini bertujuan untuk mengungkap makna dan domain leksem tebing dalam penamaan tanjak Melayu, khususnya pada Tanjak Tebing Tinggi, Tebing Runtuh, dan Tebing Laksamana, dalam konteks budaya masyarakat Melayu melalui pendekatan semantik inkuisitif. Penelitian ini menggunakan metode deskriptif kualitatif. Data berupa frasa, kalimat, dan gambar yang berkaitan dengan nama-nama tanjak Melayu dikumpulkan melalui teknik observasi, wawancara, dan dokumentasi, dengan sumber data berasal dari buku Destar Alam Melayu (Asal-Usul, Sejarah dan Penggunaan) karya Johan Iskandar serta wawancara dengan narasumber dari komunitas Serai Serumpun. Analisis data dilakukan melalui tiga tahap, yaitu semantik skrip, semantik kognitif, dan semantik inkuisitif. Hasil penelitian menunjukkan bahwa leksem tebing dimaknai sebagai simbol pertahanan yang merepresentasikan keteguhan, perlindungan, dan daya tahan dalam budaya Melayu. Secara spesifik, Tanjak Tebing Tinggi dimaknai sebagai simbol pertahanan dan berada pada domain kekuasaan, Tanjak Tebing Runtuh dimaknai sebagai simbol keberhasilan dalam mempertahankan wilayah, dan Tanjak Tebing Laksamana dimaknai sebagai simbol pemimpin yang berhasil dalam mempertahankan wilayah, yang keduanya berada pada domain jasa. Penamaan tanjak berleksem tebing bersifat peristiwa karena didasarkan pada pengalaman historis dan simbolik masyarakat Melayu dalam konteks pertahanan dan kepemimpinan.